ISLAM POLITIK DI PAPUA: RESISTENSI DAN TANTANGAN MEMBANGUN PERDAMAIAN - Idrus Al-Hamid (Millah: Journal of Religious Studies, 2013)
This paper reflects the present of political Islam and Cultural Islam in recent Papua. The groups of Islamic movements sign that number of Moslem population is growing in line with the coming of the Moslem immigrant from other areas of Indonesia. The consequences are facilities such as mosques, Islamic institutions, Islamic schools I educations are increasing. The Papuan Moslem Assembly which represents the indigenous Muslim organizations discourages the newly came Islamic organizations such as Hizbut Tahrir Indonesia (HTI), Salafi, even Laskar Jihad, to utilize the hardline links and teachings in preaching (dakwah). From the encounter side or non-Muslim, indigenous Papua and particularly Christian that phenomena leads to the Islamization which is warning of the peace building. This paper also suggests to create a friendly teachings I mission and to move closely the dakwah into the local/ indigenous people within community. The diversity of Papuan identity calls the Islamic preachers to have more respects and cultural understanding during the teachings